Assessing the cytotoxic potential of glycoalkaloidic extract in nanoparticles against bladder cancer cells. (5th August 2019) - Miranda, Mariza A; Marcato, Priscyla D; Carvalho, Ivana P S; Silva, Letícia B; Ribeiro, Diego L; Amaral, Robson; Swiech, Kamilla; Bastos, Jairo K; Paschoal, Jonas A R; dos Reis, Rodolfo B; Bentley, Maria V L B
Abstract: Objective: This study proposed to use the nanotechnology to deliver glycoalkaloidic extract (AE) to bladder cancer cells, evaluating their activity in 2D and 3D models and the biological mechanism of cell death. Methods: NPs were prepared by nanoprecipitation method using polylactic acid (PLA) and characterized considering their size, charge, particle concentration and stability. The cytotoxicity was evaluated in 2D and 3D model, and the apoptosis and cell cycle were investigated using flow cytometry. Key findings: NPs loading AE (NP-AE) had diameter around 125 ± 6 nm (PdI <0.1) and negative charge. The encapsulation efficiency of SM and SS was higher than 85% for both compounds. The obtained formulation showed a significant in-vitro cytotoxic effect against RT4 cells in a dose-dependent manner with IC50 two fold lower than the free AE. The cytotoxic effect of NP-AE was mediated by apoptosis and cell cycle arrested in the S phase. RT4 cells cultured under 3D conditions exhibited a higher resistance to the treatments (IC50 ~ three fold higher than in 2D cell culture). Conclusion: The NP-AE might be a promising nanocarrier to load and deliver glycoalkaloids against bladder cancer.